The Government's Policies on the Prevention of COVID-19 Transmission Impacting Household Food Security in Indonesia - Putu Emy Indrayani; Dyah Suryani; Prisilia Oktaviyani; Suyitno Suyitno; Sagung Putri ME Purwani; Ni Ketut Supasti Dharmawan (Jurnal Penelitian Pendidikan IPA, 2023)
Household food security is an essential issue for a country and has become a national issue in poor and developing countries worldwide during the COVID-19 pandemic. Various problems could arise if household food-nutrition needs are not met. This study aims to explore factors related to household food security during the COVID-19 pandemic in Indonesia. A systematic literature review that was used twelve articles. Three electronic databases (Google Scholar, ProQuest, and ScienceDirect) were used to find the articles between January 2020 to April 2023. The original articles were selected based on the PRISMA-P flowchart model. The results show the socio-demographic (sex of household’s head, age, education, literacy) and socio-economic (occupation, income, wealth, area of living) factors influencing household food security. Households having a male head of household, good literacy, and an adequate economy have a significant effect on having nutritious food security during COVID-19 pandemic. These findings recommend that the central government of Indonesia provide financial assistance to food-insecure households, improve access to food, and promote healthy food products